Psykoterapian vaikutukset aivotoimintoihin masennustilassa. - Perämäki Tapio; Koivisto Mika (Suomen Lääkäriliitto, 2022)
Modern brain imaging methods allow researchers to measure the effects of psychotherapy on brain function at system level. We review the influences of psychotherapy on brain function in major depression after cognitive-behavioral or interpersonal psychotherapies. Brain imaging in rest shows that the primary effects of psychotherapy are the decrease of  over-activity in prefrontal cortex and increase of activity in limbic regions, for example in anterior cingulate and amygdala. During cognitive-emotional processing tasks, the activation levels of prefrontal cortex and limbic regions decrease in response to negative stimuli and increase in response to positive stimuli after successful psychotherapy. Thus, psychotherapy influences the activity of the brain areas which are involved in emotional processing by normalizing their functioning. A low activation level in anterior cingulate before the onset of psychotherapy predicted a good response to treatment. In future it may be possible to make use of brain imaging in planning therapeutic interventions for individuals suffering from specific types of depressive symptoms.